Characteristics of Eye Tumor in Children - Pieter Juanarta; Mohamad Rinaldi Dahlan; Andri Rezano (Althea Medical Journal, 2017)
Background: Eye tumors are commonly found and fatal among pediatric patients. The immediacy of management depends on the diagnosis, and is increased when the patient’s characteristics are known. This study aims to describe the characteristics of pediatric patients diagnosed with eye tumors.Methods: This is a descriptive retrospective study using secondary data involving 102 medical records of pediatric patients diagnosed with eye tumors in the National Eye Center Cicendo Eye Hospital Bandung in the period from January 2013 to December 2014.Results: The characteristics of 102 subjects: 54 (52.9%) were female, 59 (57.8%) were 1 to 4 years old, and 79 (77.5%) were from West Java. The characteristics of the tumors: 42 (41.2%) presented with a chief complaint of leukocoria, 73 (71.6%) were malignant, 68 (66.7%) were retinal, and the most common management was surgery (64.7%). The most common malignant tumor was retinoblastoma (93.2%) while the most common benign tumor was dermoid cyst (31%).Conclusion: Patients were frequently 1–4 years old and the most common diagnosis were retinoblastoma and dermoid cyst. DOI: 10.15850/amj.v4n1.970